1994
DOI: 10.1557/proc-366-201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Electrokinetics in Porous Media

Abstract: In brine-saturated porous media the existence of a space-charge layer at the solid/liquid interface leads to a coupling between fluid and electric currents. This coupling is seen as a streaming potential (STP) across a porous plug when the fluid flows through it, or conversely, as electroosmosis (ELO) of the fluid when an electric field is applied. The magnitude of these electrokinetic effects depends on the thickness of the space-charge layer relative to the pore size, which in turn depends upon the salinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…extrapolate the frequency-dependent streaming potential value to the dc limit. This is done for the purposes of determining the zeta or surface potentials (7,8). Low-frequency measurements are also used to determine the effective pore size and hydraulic permeability (9).…”
Section: Introductionmentioning
confidence: 99%
“…extrapolate the frequency-dependent streaming potential value to the dc limit. This is done for the purposes of determining the zeta or surface potentials (7,8). Low-frequency measurements are also used to determine the effective pore size and hydraulic permeability (9).…”
Section: Introductionmentioning
confidence: 99%
“…Equation [9] is the ac Helmholtz-Smoluchowski equation. The frequency at which inertial terms start to dominate over viscous terms is often called the transition frequency and for a capillary model is given by…”
Section: Figmentioning
confidence: 99%
“…Therefore, low frequencies should be avoided in fitting the frequency-dependent coupling coefficient theory, Eq. [9], to the transient data. It is also useful to look at the streaming potential and pressure spectra individually to see at what frequency the signal-to-noise ratio starts to skew the coupling coefficient data.…”
Section: Fig 12mentioning
confidence: 99%
See 1 more Smart Citation
“…enhanced. Electro-osmotic flows in porous media are also of significance and arise in both biological systems and industrial systems and have been shown to markedly influence transport rates [12]. The classical approach to simulating transport in porous media is the Darcy model which is valid for viscousdominated, low Reynolds number flows.…”
Section: Introductionmentioning
confidence: 99%